Differentiated interfacial regulation by a bio-based polysaccharide depressant for sustainable Cu–Mo flotation separation - Yimin Zhu; Yuning Ma; Hui Li; Wenjie Han; Jie Li; Jie Liu (Minerals Engineering, 2026)

Integrated hydrogen system analysis across the resource-environment-economy nexus: a case study of China - Maximilian Arras; Anne Yingqiu Liang; Yuning Fu; Zheng Li; Linwei Ma (Journal of Industrial Ecology, 2026)

A three-dimensional-simulation-assistant optimization of heat transfer and the influence of hot water treatment on postharvest quality, volatile flavor compounds and cuticular wax metabolisms of three cultivar mangoes - Shiyi Xiong; Yuning Zhang; Yanyan Ma; Hongliang Zhu; Guogang Chen; Jiankang Cao (Food Chemistry, 2026)

Outstanding extrinsic reversible self-healing material for commercial epoxy coating: Dynamic chemistry-based supramolecular interpenetrating polymer networks - Panhua Li; Tingting Luo; Xuanyu Lv; Yuning Shi; Bosen Zhang; Kaixuan Ma; Wanchun Guo; Kesong Tian; Xueai Li; Hui Ying Yang; Haiyan Wang (Chemical Engineering Journal, 2026)

Biomimetic sequential immuno-osteogenic regulation via a dual-drug delivery system with PDA coating on sulfonated PEEK promotes bone defect repair - Zixuan Wu; Kai Ma; Xiaoyu Guo; Zidong Wu; Zheyue Zhu; Yuning Qu; Weidong Zhu; Chengxin Li; Rui Ma; Pei Yang (Chemical Engineering Journal, 2026)

In vivo CAR-T: a paradigm shift in adoptive cell therapy from bench to beside - Yuanting Cai; Huilei Miao; Yuning Wang; Jiatong Ding; Peiwen Ma; Xiaosong Zhong; Yue Bai; Hengjia Tu; Zhongwei Xu; Guo Zhao; Zhangqiang Xiang; Shuhang Wang; et al. (Science Bulletin, 2026)

Physiological, metabolic, and transcriptional responses of contrasting sorghum (Sorghum bicolor (L.) Moench) cultivars to drought - Chunlei Zou; Junming Ma; Tao Jin; Xinyu Wang; Xiaoxia Shi; Yuning Hao; Zihao Guo; Xiaolong Wei; Chunlai Zhang; Zhijia Gai (Plant Cell Reports, 2026)

Dual-functional 3D-printed polyetheretherketone scaffolds with immunomodulatory nano‑calcium silicate/interleukin-4 coating synergistically enhance osteogenesis through macrophage M2 polarization and NF-κB pathway suppression - Xiaoyu Guo; Yanwen Su; Zixuan Wu; Zidong Wu; Kaili Liu; Junyu Yue; Yuning Qu; Kunzheng Wang; Jiankang He; Rui Ma; Pei Yang (Chemical Engineering Journal, 2025)

Lipid profiles and metabolic characteristics of Chinese tea cultivars (Camellia sinensis) with different manufacturing suitabilities by comparative lipidomics using UHPLC-Q-Exactive mass spectrometry - Le Chen; Jianqiang Ma; Linchi Niu; Yuning Feng; Zhizhen Fang; Shan Zhang; Xujiang Shan; Qianting Zhang; Qinghua Zhou; Yongwen Jiang; Haibo Yuan; Jia Li (Food Chemistry, 2025)

Neurotoxic risks of long-term environmental exposure to pesticides: a review - Yumeng Leng; Ye Zeng; Yuning Zhang; Jialin Zhang; Hao Xin; Mingyang Hou; Siman Ma; Hong Zhang (Chemico-Biological Interactions, 2025)

Collaboratively removal of phosphate and glyphosate from wastewater by a macroscopic Zr-SA/Ce-UIO-66 adsorbent: Performance, mechanisms and applicability - Zhixiang Xu; Dongshan Chen; Xingyu Duan; Yuning Chen; Caiqing Li; Siyuan Li; Yitao Ma; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2025)

Optimizing a link-based travel incentive scheme integrating personal carbon trading for low-carbon commuting - Bing Liu; Xiaolei Ma; Yuning Shi; Xiaohai Liu; Kun Gao; Qiong Tian; Wenwei Wang (Journal of Environmental Management, 2025)

Centrifuge model tests and numerical simulation on ground-borne vibration propagating and vibration reduction scheme for tunnel inner structure - Zhenghao Liu; Xianfeng Ma; Junyu Chi; Yuning Chen; Chen Wang (Tunnelling and Underground Space Technology, 2024)

Perspectives on the highly selective oxidation of copper-mediated C3N4-BiVO4 organic-inorganic hybrid catalysts and the efficient generation of reactive oxygen species - Qian Luo; Yue Chen; Yanjun Zhao; Shan He; Shirui Lv; Yuning Ma; Xintong Liu (Chemical Engineering Journal, 2024)

Novel cow dung-doped sludge biochar as an efficient ozone catalyst: Synergy between graphitic structure and defects induces free radical pathways - Yuxuan Yang; Kedong Ma; Yubo Cui; Ke Zhao; Yuning Lu; Wanjun Zhang; Peijing Kuang; Xuejun Zou (Environmental Research, 2024)

Multi-step Fracturing Radial Boreholes for Efficient Development of Unconventional Gas Reservoirs - Tianyu Wang; Zhaoquan Guo; Zhengchao Ma; Yuning Yong; Gensheng Li; Shouceng Tian (Rock Mechanics and Rock Engineering, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Target-site and non-target-site based resistance to clodinafop-propargyl in wild oats (Avena fatua L.) - Yujun Han; Ying Sun; Hong Ma; Ruolin Wang; Yuning Lan; Haifeng Gao; Zhaofeng Huang (Pesticide Biochemistry and Physiology, 2023)

Occurrence of halogenated methanesulfonic acids in water and sediment from the Hangzhou Bay, China - Fang Tao; Yujia Tan; Junwei Dai; Congrui Lu; Yadong Sha; Yi Liu; Xinxing Zhou; Qingele Hasi; Zhemin Shen; Yuning Ma (Environmental Research, 2023)

Correction to: Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2022)

Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2021)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Urine concentrations of perfluoroalkyl acids in children and contributions of dietary factors: a cross-sectional study from Shanghai, China - Juan Li; Jiafan Li; Yuning Ma; Bo Chen; Xirui Wang; Xianting Jiao; Yihui Jin; Zhemin Shen; Tao Yuan; Xiaodan Yu (Environmental Science and Pollution Research, 2021)

Reduced glycodeoxycholic acid levels are associated with negative clinical outcomes of gestational diabetes mellitus - Bo Zhu; Zhixin Ma; Yuning Zhu; Lei Fang; Hong Zhang; Hongwei Kong; Dajing Xia (Journal of Zhejiang University-SCIENCE B, 2021)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Analysis of gene expression profile in pollen development of recessive genic male sterile Brassica napus L. line S45A - Yuning Chen; Shaolin Lei; Zhengfu Zhou; Fangqin Zeng; Bin Yi; Jing Wen; Jinxiong Shen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Plant Cell Reports, 2009)